Studi Rancangan Konsep Produk Brassiere Melalui Pendekatan Nilai Emosi Dan Perasaan Menggunakan Kansei Engineering Method - Wahyuning, Caecilia Sri; Desrianty, Arie; Rahmawati, Rika (FSRD ITENAS, 2011)
Abstract Complexities of customer needs for buying or using new products ensue the need of customer oriented product designs. Customer’s emotions and feelings give influences in choosing and deciding new products, therefore these should be considered in product design processes. A brassiere is an article of clothing that covers, supports, and elevates breasts. To design the brassiere, a company needs to develop the brassiere concepts that could satisfy the women’s feelings and emotions in deciding to buy or use brassiere. Kansei Engineering is a method for translating feelings and impressions into product parameters that can